2003
DOI: 10.1586/14737175.3.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Delirium: pathophysiology, recognition, prevention and treatment

Abstract: Delirium, a clinical syndrome characterized by the acute onset of confusion, indicates that there is a disruption in physiological equilibrium that may lead to death unless quick and appropriate action is taken. Despite its frequent appearance, delirium often goes unrecognized, undetected and untreated, leading to poorer outcomes including longer lengths of hospitalization, persistent deficits in cognitive function and the need for nursing home placement following acute treatment. Prevention and treatment stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…11,12,20 During coma, the different systems of neurotransmission, such as the cholinergic and adrenergic systems, are involved in the determination of the state of consciousness 39 and may be responsible for the onset of delirium. 19,40 Delirium is a disturbance in cognitive function that is characterized by impaired attention and is associated with an altered level of consciousness and a fluctuating course. Contrary to coma, during delirium, elements of arousal and awareness are retained.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,20 During coma, the different systems of neurotransmission, such as the cholinergic and adrenergic systems, are involved in the determination of the state of consciousness 39 and may be responsible for the onset of delirium. 19,40 Delirium is a disturbance in cognitive function that is characterized by impaired attention and is associated with an altered level of consciousness and a fluctuating course. Contrary to coma, during delirium, elements of arousal and awareness are retained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mostly report on delirium in hospitalized older people, where prevalence estimates vary between 15% and 24% Marcantonio et al 2003;Ouimet et al 2007). Reported rates of incidence of delirium among older people admitted to hospitals range from 5% to 35% Ouimet et al 2007;Rabinowitz et al 2003). Dosa et al reported between 16% and 23% of possible cases of delirium in a subgroup of post-acute hospitalized older patients discharged to nursing homes depending on the diagnostic criteria used (Dosa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The mental health research in long-term care with the LTCF and HC includes depression (193), bipolar disorder (194,195), suicidal behaviors (196,197), traumatic brain injury (198)(199)(200), delirium (201,202), aggressive behavior (203)(204)(205), and cognitive impairment (206)(207)(208)(209)(210).…”
Section: Home Care and Nursing Homesmentioning
confidence: 99%